Theoretical Basis, Laboratory Evidence, and Clinical Research of Chemical Surgery of the Cornea: Cross-Linking - Amanda C. da Paz; Patrícia A. Bersanetti; Marcella Q. Salomão; Renato Ambrósio; Paulo Schor (Journal of Ophthalmology)
Corneal cross-linking (CXL) is increasingly performed in ophthalmology with high success rates for progressive keratoconus and other types of ectasia. Despite being an established procedure, some molecular and clinical aspects still require additional studies. This review presents a critical analysis of some established topics and others that are still controversial. In addition, this review examines new technologies and techniques (transepithelial and ultrafast CXL), uses of corneal CXL including natural products and biomolecules as CXL promoters, and evidence for in vitro and in vivo indirect effectiveness.